Physicochemical and biological evaluation of siRNA polyplexes based on PEGylated Poly(amido amine)s. - Vader, P; van der Aa, L; Engbersen, J; Storm, G; Schiffelers, R (2012)
PURPOSE: Use of RNA interference as novel therapeutic strategy is hampered by inefficient delivery of its mediator, siRNA, to target cells. Cationic polymers have been thoroughly investigated for this purpose but often display unfavorable characteristics for systemic administration, such as interactions with serum and/or toxicity. METHODS: We report the synthesis of a new PEGylated polymer based on biodegradable poly(amido amine)s with disulfide linkages in the backbone. Various amounts of PEGylated polymers were mixed with their unPEGylated counterparts prior to polyplex formation to alter PEG content in the final complex. RESULTS: PEGylation effectively decreased polyplex surface charge, salt- or serum-induced aggregation and interaction with erythrocytes. Increasing amount of PEG in formulation also reduced its stability against heparin displacement, cellular uptake and subsequent silencing efficiency. Yet, for polyplexes with high PEG content, significant gene silencing efficacy was found, which was combined with almost no toxicity. CONCLUSIONS: PEGylated poly(amido amine)s are promising carriers for systemic siRNA delivery in vivo.